Deterministic Application of Process-centric Law to the System-centric Requirements of Procurement Procedures - Wickens, David John (Potchefstroom Electronic Law Journal, 2021)
South Africa’s public procurement system is accorded constitutional status, establishing fundamental requirements for the operation of the system. The application of these constitutional system requirements and their interpretation in the judicial adjudication of procurement cases have highlighted the tension between the administrative, or process-centric, legal requirements and the system-centric nature of procurement procedures. The importance of a deterministic approach for procurement decision-making can be considered from two angles – the certainty of the procurer in the conformity of its own conduct and external certainty to diminish the risk of unnecessary challenge. This article revisits the foundational rationale for system-based procurement procedures and associated decision-making for its potential for finding a deterministic approach to balancing the legal requirements, both system- and process-based. These principles are tested against a selection of adjudicated outcomes to formulate practical recommendations for practitioners aimed at deterministic decision-making in the procurement process.